Assessing Moving Targets: the Impact of Transition Stages on Entrepreneurship Development - Aidis, Ruta; Sauka, Arnis (Ekonomika, 2005)
An issue that has recently gained in importance in transitional literature is the need to develop a thriving small and medium-sized enterprise (SME) sector since it can contribute significantly to innovation, job creation and economic growth. However, the specific characteristics of SMEs make them especially vulnerable to changes in the legal, social and environmental context. In this paper we are interested in the barriers that SME development encounters during different stages in the transition process. There is no consensus regarding ‘transition stages’, yet various indicators measuring certain aspects of transition progress have been developed. For this paper, we apply a selection of indicators proposed in previous research to approximate three transitional stages that would make sense from an entrepreneurship development perspective. We utilise these indicators to categorise 23 transition countries into transitional stages. On the basis of that utilisation we develop a framework in which we can identify SME development trends based on our analysis of the 25 empirical studies on constraints facing SMEs in transition countries. Our preliminary results indicate that more fundamental barriers related to legal issues are more characteristic of the early stages of transition, while more specific constraints related to human resources and skill development characterise later transition stages.